1994
DOI: 10.1113/expphysiol.1994.sp003808
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a hyposmotic shock on amino acid efflux from lactating rat mammary tissue: stimulation of taurine and glycine efflux via a pathway distinct from anion exchange and volume‐activated anion channels

Abstract: SUMMARYWe have examined the effect of a hyposmotic shock, and thus cell swelling, upon the efflux of amino acids, SO42-and 1-from lactating mammary tissue. A hyposmotic challenge increased the efflux of taurine and glycine via a 4,4'-diisothiocyanatostilbene-2,2'-disulphonic acid (DIDS)-sensitive pathway. It appears that these amino acids do not exit via an anion-exchange mechanism following cell swelling because sulphate efflux, which uses a DIDS-sensitive exchange mechanism, was unaffected. The hyposmotic-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 31 publications
2
47
0
Order By: Relevance
“…The mechanism of taurine release shares a number of characteristics with I Cl,vol and in whole cell patch clamp experiments a significant permeability to large organic anions, such as taurine, gluconate and aspartate could be demonstrated, thus I Cl,vol seems in many cells to be the major swelling-activated pathway for taurine efflux [31]. In EATC however, swelling-induced taurine and Cl -efflux pathways appear to have different pharmacological profiles suggesting separate channels [67] (Table 1), as also suggested in rat mammary tissue [68], HeLa cells [69] and mammalian liver cells (Junankar, PR and Kirk, K, this issue) . In addition, swelling-induced taurine release without any Cl -channel activity has been demonstrated in Xenopus laevis oocytes expressing anion channels and transporters [70]…”
Section: Characteristics Of the Cell Swelling-activated Taurine Effluxmentioning
confidence: 59%
“…The mechanism of taurine release shares a number of characteristics with I Cl,vol and in whole cell patch clamp experiments a significant permeability to large organic anions, such as taurine, gluconate and aspartate could be demonstrated, thus I Cl,vol seems in many cells to be the major swelling-activated pathway for taurine efflux [31]. In EATC however, swelling-induced taurine and Cl -efflux pathways appear to have different pharmacological profiles suggesting separate channels [67] (Table 1), as also suggested in rat mammary tissue [68], HeLa cells [69] and mammalian liver cells (Junankar, PR and Kirk, K, this issue) . In addition, swelling-induced taurine release without any Cl -channel activity has been demonstrated in Xenopus laevis oocytes expressing anion channels and transporters [70]…”
Section: Characteristics Of the Cell Swelling-activated Taurine Effluxmentioning
confidence: 59%
“…In Ehrlich ascites tumour cells subjected to a hypoosmotic shock taurine efflux was inhibited by DIDS and activated by arachidonic acid whereas 36 Cl -efflux was largely unaffected by DIDS and inhibited by arachidonic acid [39]. Similarly, in HeLa cells, the hypoosmotically-activated taurine efflux pathway was reportedly more sensitive to inhibition by DIDS than was either I Cl, swell or hypoosmotically-activated 125 I -efflux [40].…”
Section: CLmentioning
confidence: 95%
“…Shennan and coworkers have presented evidence that in rat mammary tissue osmotic swelling induces the efflux of taurine while having little effect on the efflux of either I -or D-aspartate [36,37]. In another recent study Bröer and colleagues report that in Xenopus oocytes expressing different exogenous proteins, exposure to hypoosmotic media stimulates an efflux of taurine, while having little effect on either the efflux of 36 …”
Section: Are There Swelling-activated Channels With a Preference For mentioning
confidence: 99%
“…The efflux of radiolabelled taurine from the cells was measured by the sequential addition and removal of 2 ml of medium (see figure legends for precise details of composition) at 1 min intervals at 37 o C. The cells were lysed after the wash-out period by incubating in 2 ml of distilled water for at least 3 h. The wash-out samples and the lysate were prepared for counting by adding 10 ml of UltimaGold liquid scintillation cocktail. The fractional efflux for each collection period was calculated according to the method descibed by Shennan et al [8]. Preleminary experiments established that taurine efflux from MDA-MB-231 and MCF-7 cells, measured under isosmotic conditions, followed first order kinetics and thus could be described by a single mono-exponential equation (results not shown).…”
Section: Taurine Effluxmentioning
confidence: 99%
“…On the one hand it has been suggested that swelling-induced taurine release utilizes volume-activated chloride channels (eg see [5,6]). On the other hand there is evidence suggesting that volume-activated taurine efflux is independent from chloride channels (eg see [7][8][9]). …”
Section: Introductionmentioning
confidence: 99%